Modern ICT for Agricultural Development and Risk Management in Smallholder Agriculture in India. - Mittal, Surabhi (International Maize and Wheat Improvement Center, 2012)
Usually the agricultural sector, and in particular farmers, are highly vulnerable to risks due to high variability in climatic conditions and to market uncertainties. The farmer s exposure to risk and uncertainty is often aggravated by lack of information about weather, inputs, farm management practices or market prices, and this lack of information has an adverse impact on crop production and income. Some of these risks, for example the risk of a bad monsoon, affect agriculture as a whole, while other risks vary from region to region, and the severity of their effect depends on an individual farmer s knowledge and ability to cope. The evidence suggests that a farmer who receives quality, up to date information, and who has the ability to use that information, is able to lessen the effect of these risks.